ASURANSI KONVENSIONAL DALAM PANDANGAN HUKUM ISLAM - Bakar, H. Abu (E-Journal Widya Yustisia, 2005)
Conventional Insurance form agreement between two side or more which guarantor side fastes self endured with accept insurance premium to give detriment replacement to endured because detriment, damage, hope for profit loss, or law responsible with third side which able endured suffered that emerge from uncertain event or to give payment for a life person or died person.Uncertain substance, premium that unbalance with loss out, fund investment that collected in insurance, company with remainder way causedby conventional insurance doesnât correct with law expert.View of Islam law toward conventional insurance pictured from scholar of Islam viewed and an intellectual Moslem that is forbidden viewed, allowed, abstain from commercial insurance and allowed social insurance and conventional insurance viewed as subhat.